Key success factors in the continuous use of MOOC education in South Korea. (31st January 2022) - Park, Thomas Jin; Whang, Jaehoon; Watts, Sean; Han, Dong-Gyun
Society is facing a paradigm shift where general education is moving towards lifelong education. Massive open online course (MOOC) is the leading online education with large-scale open classes. South Korea has localised 1, 340 MOOCs known as K-MOOCs. However, K-MOOCs are not being managed effectively, and are generally low-level lectures compared to MOOCs. The variance-based structural equation modelling (SEM) using the partial least squares (PLS) model was applied for data analysis. Online surveys and analysis of 224 respondents studied 14 hypotheses and analysed eight factors to improve K-MOOC operation in South Korea. Findings indicated 'authentic learning' positively affects 'learning transfer'; 'gamification', 'teaching presence' and 'reputation' positively affect 'satisfaction' and 'commitment'. 'Learning transfer' and 'satisfaction' impacts 'continuous use intention'. Furthermore, 'commitment' positively affects 'satisfaction', and 'continuous use intention'. This research suggests that these factors must be taken into account when constructing teaching methods and educational content to improve K-MOOCs continuous usage.